IMPLEMENTASI PROGRAM ASURANSI USAHA TANI PADI (AUTP) DI KECAMATAN KEDUNGPRING KABUPATEN LAMONGAN - Risca Evia Nuraini; Ananta Prathama (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
The purpose of this study was to describe and determine the implementation of the Rice Farming Business Insurance Program (AUTP) in Kedungpring District, Lamongan Regency. The theory used in this research is the implementation model theory by Edward III. This type of research uses descriptive qualitative. The results of this study indicate that: (1) The focus of communication in the implementation of the Rice Farmer Business Insurance Program (AUTP) in Kedungpring District, Lamongan Regency has not been implemented properly. This happens because there are still inconsistencies in the coordination and communication of the Office of Food Crops, Horticulture, and Plantations of Lamongan Regency to Field Extension Officers and to the community in Kedungpring District; (2) Resources are well implemented; (3) the disposition in the implementation of the Rice Farming Business Insurance Program (AUTP) in Kedungpring District, Lamongan Regency can be said to have been implemented well; (4) the bureaucratic structure in the implementation of the AUTP program in Kedungpring District can be said to have not been implemented properly because there is no work flow arrangement for field officers.